1994
DOI: 10.1021/bi00209a009
|View full text |Cite
|
Sign up to set email alerts
|

Eight Histidine Residues Are Catalytically Essential in a Membrane-Associated Iron Enzyme, Stearoyl-CoA Desaturase, and Are Conserved in Alkane Hydroxylase and Xylene Monooxygenase

Abstract: The eukaryotic fatty acid desaturases are iron-containing enzymes that catalyze the NAD-(P)H- and O2-dependent introduction of double bonds into methylene-interrupted fatty acyl chains. Examination of deduced amino acid sequences for the membrane desaturases from mammals, fungi, insects, higher plants, and cyanobacteria has revealed three regions of conserved primary sequence containing HX(3 or 4)H,HX(2 or 3)HH, and HX(2 or 3)HH. This motif is also present in the bacterial membrane enzymes alkane hydroxylase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
649
1
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 722 publications
(678 citation statements)
references
References 41 publications
21
649
1
7
Order By: Relevance
“…Kyte-Doolittle analysis of these other proteins revealed the presence of multiple hydrophobic sequences that may span the cellular membrane (26). Likewise, previous Kyte-Doolittle hydropathy analysis suggested that DesA3 might contain up to three hydrophobic domains (5).…”
Section: Topology Of Membrane Desaturasesmentioning
confidence: 86%
See 1 more Smart Citation
“…Kyte-Doolittle analysis of these other proteins revealed the presence of multiple hydrophobic sequences that may span the cellular membrane (26). Likewise, previous Kyte-Doolittle hydropathy analysis suggested that DesA3 might contain up to three hydrophobic domains (5).…”
Section: Topology Of Membrane Desaturasesmentioning
confidence: 86%
“…One product of this reaction, oleic acid, is an essential constituent of mycobacterial membrane phospholipids and triglycerides (5,(23)(24)(25). Thus DesA3 is suggested to be a target of isoxyl (also known as thiocarlide), an anti-tuberculosis drug that inhibits the synthesis of oleic and mycolic acids (5).DesA3 shares the conserved eight His motif found in membrane acyl-lipid and acyl-CoA desaturases and in the related bacterial membrane enzymes alkane hydroxylase and xylene monooxygenase (5,(26)(27)(28). By this assessment, DesA3 is likely to be an integral membrane diiron enzyme.…”
mentioning
confidence: 99%
“…The positions of the 11 conserved differences determined from the alignment are shown in Figure 2, overlaid on a topological model established for membrane-bound desaturases (11). It is notable that all but 2 of the positions are predicted to be on the cytosolic side of the endoplasmic reticulum and 7 out of the 11 positions are within 12 amino acids of one of three His boxes which are thought to be involved in binding a diiron cluster at the active site of these enzymes.…”
Section: Crep1mentioning
confidence: 99%
“…Full-length sequence of what was likely to be the conserved ∆9 desaturase (CL11, JQ619632) was also obtained. All encoded protein sequences were confirmed as desaturases, as they contained the eight conserved histidine residues that form the 'histidine boxes' that are essential for desaturase activity 21 , were of length between 327-354 amino acids and were aligned with the desaturases of mammals and insects that utilize CoA-linked substrates ( Supplementary Fig. S2).…”
Section: Resultsmentioning
confidence: 99%